Combined RNAseq and ChIPseq Analyses of the BvgA Virulence Regulator of Bordetella pertussis - Loïc Coutte (American Society for Microbiology, 2020)
ABSTRACT Bordetella pertussis regulates the production of its virulence factors by the two-component system BvgAS. In the virulence phase, BvgS phosphorylates BvgA, which then activates the transcription of virulence-activated genes (vags). In the avirulence phase, such as during growth in the presence of MgSO4, BvgA is not phosphorylated and the vags are not expressed. Instead, a set of virulence-repressed genes (vrgs) is expressed. Here, we performed transcriptome sequencing (RNAseq) analyses on B. pertussis cultivated with or without MgSO4 and on a BvgA-deficient Tohama I derivative. We observed that 146 genes were less expressed under modulating conditions or in the BvgA-deficient strain than under the nonmodulating condition, while 130 genes were more expressed. Some of the genes code for proteins with regulatory functions, suggesting a BvgA/S regulation cascade. To determine which genes are directly regulated by BvgA, we performed chromatin immunoprecipitation sequencing (ChIPseq) analyses. We identified 148 BvgA-binding sites, 91 within putative promoter regions, 52 within open reading frames, and 5 in noncoding regions. Among the former, 32 are in BvgA-regulated putative promoter regions. Some vags, such as dnt and fhaL, contain no BvgA-binding site, suggesting indirect BvgA regulation. Unexpectedly, BvgA also bound to some vrg putative promoter regions. Together, these observations indicate an unrecognized complexity of BvgA/S biology. IMPORTANCE Bordetella pertussis, the etiological agent of whooping cough, remains a major global health problem. Despite the global usage of whole-cell vaccines since the 1950s and of acellular vaccines in the 1990s, it still is one of the most prevalent vaccine-preventable diseases in industrialized countries. Virulence of B. pertussis is controlled by BvgA/S, a two-component system responsible for upregulation of virulence-activated genes (vags) and downregulation of virulence-repressed genes (vrgs). By transcriptome sequencing (RNAseq) analyses, we identified more than 270 vags or vrgs, and chromatin immunoprecipitation sequencing (ChIPseq) analyses revealed 148 BvgA-binding sites, 91 within putative promoter regions, 52 within open reading frames, and 5 in noncoding regions. Some vags, such as dnt and fhaL, do not contain a BvgA-binding site, suggesting indirect regulation. In contrast, several vrgs and some genes not identified by RNAseq analyses under laboratory conditions contain strong BvgA-binding sites, indicating previously unappreciated complexities of BvgA/S biology.